A Thematic Digital Quran Learning Model in Islamic Religious Education - Affandi, Lukman; Rahmat, Munawar; Supriadi, Udin (Jurnal Pendidikan Islam, 2021)
In the digital era, learning activity requires several competencies including several applications to use digital media like digital Quran. This research is aimed at analyzing the strategies to increase religious substance in Islamic religious education courses for students Majoring in PAI (Pendidikan Agama Islam/Islamic Religious Education), Universitas Pendidikan Indonesia, through the Digital Quran. This study applied a survey approach involving 104 students in their third semester. Data were analyzed using multiple linear regression. The results showed that the thematic learning of the digital Quran, which was carried out simultaneously, could increase students’ religious substance with Fcount 22.477 > Ftable 3.09, significance value 0.05, and probability 0.000